Morals in the United States of America: Are they in their death throes? - Cook, John A. (Annales. Etyka w Życiu Gospodarczym, 2019)
This article explores the ethics of large complex systems in the United States of America in three major case studies: the food industry, the pharmaceutical industry and the political/governmental institutions. Using the simple Aristotelian heuristic of good sense, good character and good will, the conclusion is that ethics is not a high priority due in large part to the relentless pursuit of large sums of money at any cost.